Photosynthetic production of α-farnesene by engineered Synechococcus elongatus UTEX 2973 from carbon dioxide - Rautela A.; Yadav I.; Gangwar A.; Chatterjee R.; Kumar S. (My University, 2025)
Cyanobacteria are the prospective biosolar cell factories to produce a range of bioproducts through CO2 sequestration. Farnesene is a sesquiterpene with an array of applications in biofuels, pest management, cosmetics, flavours and fragrances. This is the first time a codon-optimized farnesene synthase (AFS) gene is engineered into the genomic neutral site of Synechococcus elongatus UTEX 2973 for farnesene synthesis through its endogenous methylerythritol phosphate (MEP) pathway, rendering UTEX AFS strain. Similarly, bottleneck gene(s) of the MEP pathway, 1-deoxy-D-xylulose-5-phosphate synthase (dxs) and/or fusion of isopentenyl diphosphate isomerase and farnesyl diphosphate synthase (idispA) were engineered engendering UTEX AFS